2006
DOI: 10.1007/s10397-006-0178-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic hysterectomy and ureteric injury: a comparison of the initial 275 cases and the last 1,000 cases using staples

Abstract: We retrospectively analysed our first 1,275 laparoscopic hysterectomies for ureteric injuries. All patients scheduled for hysterectomy in two private gynaecological practices in Sydney and Adelaide over the past decade were offered laparoscopic hysterectomy using a linear cutter stapling device for securing uterine vascular pedicles. The stapling of the uterine vascular pedicles resulted in the injury of four ureters in the first 275 cases (1.45%), whereas in the subsequent 1,000 cases there was only one such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…16,21 But there are studies now which state that in experienced hands and with a perfect technique TLH is not associated with any increase in major complications and even ureteric injuries are not more. 22,23 Effect of AH and TLH on post-operative vaginal length was compared which showed that it was shorter following AH and patients who have undergone TLH have better outcome related to certain sexual function parameters. 24,25 Conversion rate in present study was 1.69% for laparotomy and 1.69% for vaginal hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…16,21 But there are studies now which state that in experienced hands and with a perfect technique TLH is not associated with any increase in major complications and even ureteric injuries are not more. 22,23 Effect of AH and TLH on post-operative vaginal length was compared which showed that it was shorter following AH and patients who have undergone TLH have better outcome related to certain sexual function parameters. 24,25 Conversion rate in present study was 1.69% for laparotomy and 1.69% for vaginal hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, large numbers would be required to show a difference given the rarity of this complication. Other large observational studies have shown no increase in ureteric injury for TLH compared to AH for the latter half of the data collection, which they attributed to surgeons completing the learning curve …”
Section: Reasons For Slow Implementationmentioning
confidence: 92%
“…The general incidence of ureteric injury, irrespective of the pathology, in abdominal hysterectomy is 1.3–2.2%, in vaginal hysterectomy is 0.03%, and in conventional laparoscopic hysterectomy, it is 1.37%. [ 1 – 3 ]…”
Section: Introductionmentioning
confidence: 99%